2007
DOI: 10.1029/2006ja012105
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced high‐altitude polar cap plasma and magnetic field values in response to the interplanetary magnetic cloud that caused the great storm of 31 March 2001: A case study for a new magnetospheric index

Abstract: [1] The magnetospheric electron number density and the magnetic field strength near 8 R E over the polar cap increased dramatically after the arrival of an interplanetary magnetic cloud on 31 March 2001. These parameters were determined with high accuracy from the plasma resonances stimulated by the Radio Plasma Imager (RPI) on Imager for Magnetopause-to-Aurora Global Exploration (IMAGE) near apogee during both quiet (30 March 2001) and disturbed (31 March 2001) days. The quiet day and disturbed day values wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 41 publications
(59 reference statements)
3
15
0
Order By: Relevance
“…While this high correlation was shown to hold at 1 AU, this correlation is also maintained at lower heliospheric distances , and at large distances (Fainberg and Osherovich, 2002). Thus one advantage of using QI is that, as a global parameter, QI follows closely the activity cycle of the Sun with in situ measurements in the heliosphere (Leitner et al, 2005;Osherovich et al, 2007). It was shown by Leitner et al (2009a) that during the recent exceptionally quiet solar cycle minimum the average QI values are lower than in two previous minima (1976 and 1995).…”
Section: Introductionmentioning
confidence: 93%
“…While this high correlation was shown to hold at 1 AU, this correlation is also maintained at lower heliospheric distances , and at large distances (Fainberg and Osherovich, 2002). Thus one advantage of using QI is that, as a global parameter, QI follows closely the activity cycle of the Sun with in situ measurements in the heliosphere (Leitner et al, 2005;Osherovich et al, 2007). It was shown by Leitner et al (2009a) that during the recent exceptionally quiet solar cycle minimum the average QI values are lower than in two previous minima (1976 and 1995).…”
Section: Introductionmentioning
confidence: 93%
“…They provide convenient ways to represent the plasma environment around the Earth. Empirical models are important for developing physics-based numeric models as well, since they provide baseline predictions against which to measure their performance (Siscoe et al 2004) and against which plasma density variations can be evaluated, particularly during magnetic storms (e.g., Tu et al 2007;Osherovich et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigation based on the radio plasma imager (RPI) [ Reinisch et al , 2000] on the Imager for Magnetopause‐to‐Auroral Global Exploration (IMAGE) satellite [ Burch et al , 2001] have shown that the polar cap electron density N e increases with geomagnetic activity [e.g., Nsumei et al , 2003; Tu et al , 2004, 2007; Osherovich et al , 2007]. The finding from IMAGE RPI observations is consistent with earlier studies using DE 1 and Polar satellite observations, as well as numerical simulations [e.g., Yau et al , 1985; Moore et al , 1999; Schunk and Sojka , 1997].…”
Section: Introductionmentioning
confidence: 99%